Memory Effect of the Southern Atlantic Subtropical Dipole - Santis, Wlademir (2020)
The South Atlantic subtropical dipole is the dominant mode of coupled variability in the South Atlantic, connecting sea level pressure and sea surface temperature. Previous studies have shown its great relevance to the climate conditions over South America and West Africa. We have used several numerical experiments with the Hybrid Coordinate Ocean Model to investigate the effects that an austral winter-spring dipole asserts on the South Atlantic. We explore the interaction between SST anomalies and the formation of the fossilized mixing region, which preserve temperature anomalies underneath the summer mixed layer, until they feed back to SST after the next autumn. It was found that, through this process, there is a memory effect that restores temperature anomalies from an austral winter–spring dipole back to the austral winter of the following year. The dominant mechanisms are the contribution from entrainment and surface net heat flux (NHF). Entrainment is mostly controlled by vertical temperature gradient anomalies, while surface NHF is controlled by interactions of climatological ocean heat loss and anomalies of mixed layer thickness. Our results suggest that the combined effect of entrainment and surface NHF is different in the southwest and northeast dipole regions, leading to differences in both intensity and timing of SST anomalies. Turbulent and nonlinear processes are most important to reduce entrainment in the southwest dipole region and to increase the memory effect asymmetry.